Drosophila cytoplasmic dynein, a microtubule motor that is asymmetrically localized in the oocyte (The Rockefeller University Press, 1994)
The unidirectional movements of the microtubule-associated motors, dyneins, and kinesins, provide an important mechanism for the positioning of cellular organelles and molecules. An intriguing possibility is that this mechanism may underlie the directed transport and asymmetric positioning of morphogens that influence the development of multicellular embryos. In this report, we characterize the Drosophila gene, Dhc64C, that encodes a cytoplasmic dynein heavy chain polypeptide. The primary structure of the Drosophila cytoplasmic dynein heavy chain polypeptide has been determined by the isolation and sequence analysis of overlapping cDNA clones. Drosophila cytoplasmic dynein is highly similar in sequence and structure to cytoplasmic dynein isoforms reported for other organisms. The Dhc64C dynein transcript is differentially expressed during development with the highest levels being detected in the ovaries of adult females. Within the developing egg chambers of the ovary, the dynein gene is predominantly transcribed in the nurse cell complex. In contrast, the encoded dynein motor protein displays a striking accumulation in the single cell that will develop as the oocyte. The temporal and spatial pattern of dynein accumulation in the oocyte is remarkably similar to that of several maternal effect gene products that are essential for oocyte differentiation and axis specification. This distribution and its disruption by specific maternal effect mutations lends support to recent models suggesting that microtubule motors participate in the transport of these morphogens from the nurse cell cytoplasm to the oocyte.